Effect of a polyp detection poster on detection of sessile serrated lesions: a prospective controlled study - Shaukat, Aasma; Rex, Douglas K.; Shyne, Michael; Church, Timothy R.; Moscatelli, Joseph P.; Colton, Joshua B. (Endoscopy International Open, 2022)
Background and study aims Colonoscopy is effective in reducing the incidence of colorectal cancer, but interval cancers remain a concern and their occurrence mainly is thought to be due to poor detection of sessile serrated lesions (SSLs) and advanced neoplasia (AN). Currently there are no low-cost, easy-to-implement tools to improve detection of difficult-to-detect polyps. Our aims were to compare the detection rate for SSLs and AN between two groups of endoscopists at a large community practice, one of which received an intervention of a polyp detection poster displayed over the monitor in their endoscopy suite for 6 months. We compared preintervention and post-intervention detection rates in the intervention and control groups.Methods This was a convenience case control quality improvement project. For 6 months, a 2’ × 3’ poster of pictures of SSLs and advanced neoplasia was displayed over the monitor for 44 endoscopist in a large community gastroenterology practice in the Minneapolis/St.Paul area, while another 44 physicians performed colonoscopy in the usual fashion without the poster. The endpoints were improvement in detection rates for SSLs and AN preintervention and post-intervention between the control and intervention groups.Results During the study, 88 endoscopists performed 54,861 colonoscopies. At least one adenoma was detected in 41.3 % of patients, one or more SSLs in 11.4 %, and AN in 10.6 %. During the intervention period, the SSL detection rates were 10.9 % and 12.3 % for the control and intervention groups and for AN, the detection rates were 10.4 % and 10.75 % for the two groups, respectively. Exposure to the polyp detection poster significantly changed SSL detection for the intervention group relative to the control group (likelihood ratio test P < 0.001). No significant effect of the intervention was observed for detection of AN, right-sided AN or left-sided AN, or adenoma detection rate.Conclusions Placement of a polyp detection poster above the endoscopy video monitor increased detection of SSL but not AN.